An Analysis Of Teachers’ Strategies In Teaching Reading Comprehension - I Gede Putu Apriasa; Siti Rodiyah; Artipah Artipah; Deny Gunawan Susandi (CV. ULIL ALBAB CORP, 2024)
This research aims to find out and analyze the strategies used by English teachers in Class Bhinneka Tunggal Ika Belitang II Vocational School Ogan Komering Ulu Timur. This research investigates the strategies teachers use in their teaching activities. This is caused by the use of old and traditional strategies that teachers usually apply in their daily activities. A qualitative approach was used in this research. The sample for this research was two English teachers. This research uses two data collection techniques: classroom observation and interviews. The findings show that the strategies used by teacher 1 to teach reading comprehension are Identifying the purpose of reading, reading aloud, Skimming, Scanning, Taking Notes, Highlighting, getting the main idea, Translating, Repeating, Analyzing Vocabulary and Summarizing. Meanwhile, the strategy used by teacher 2 is also similar to teacher 1, the difference lies in silent reading. Then the research question concerns students' responses to the strategies used by the teacher. The findings were that students responded positively to the English teacher's strategies even though they had several obstacles. Students participate in discussions and answer questions. Because the teacher points to the students one by one.